Teknik Reframing Melalui Konseling Kelompok Untuk Meningkatkan Regulasi Diri Siswa MTSN 3 Banda Aceh - Khaira, Wanty; Yola, Nadila Vita (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
The purpose of this study was to evaluate the effectiveness of reframing techniques through group counseling in improving students' self-regulation, good self-regulation tends to have better emotional control. However, some students at MTsN 3 Banda Aceh have difficulty in managing self-regulation. This quantitative study with a pre-experimental approach used a one group pretest-posttest design. A total of 30 students who had difficulty in self-regulation were selected as samples through purposive sampling. Measurements were taken using a self-regulation scale before and after three treatment sessions or group counseling treatments with reframing techniques. The results showed a significant increase in students' self-regulation, with an average score increasing from 42.83 in the pretest to 84.83 in the posttest and a t-value of 54.222 greater than t-table of 2.015 and a sig level (2-tailed ) <significance level of 0.000 <0.05. t-count is greater than t-table at a significance level of 0.05. From the research results, it can be concluded that the reframing technique through group counseling is effective in improving students' self-regulation